Revisiting the Role of Music in Medical Recovery: A Library Research Perspective - Laura Pranti, Tutom; Alexander, Chelum; Asrul Asshadi, Mohamad Morni (2025)
Across contemporary medicine, music emerges as a powerful therapeutic tool, offering measurable benefits in neurological and physical rehabilitation. Utilizing a comprehensive library research methodology, this study systematically examines scholarly articles, academic books, and scientific theses to synthesize both conceptual perspectives and empirical findings. Evidence reveals that music actively stimulates cognitive, emotional, and motor functions, particularly supporting recovery in stroke patients. The research underscores music therapy’s capacity to foster neuroplasticity and emotional resilience, making it a viable complementary intervention in rehabilitative and clinical care. By bridging scientific rigor and artistic expression, music therapy is affirmed as integral to holistic patient recovery and health.